Canadian travel survey, travel in Canada, by province of origin and destination and intraprovincial travel - Statistics Canada (Government of Canada, 2017)
This table contains 111 series, with data for years 1980 - 1996 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...), Travel duration (3 items: Total, same day and overnight travel; Same day; Overnight), Type of travel (3 items: Province of origin; Province of destination; Intraprovincial travel).